A Rare Case of Type II Odontoid Fracture With Bilateral Vertebral Arteries Occlusion Without Neurological Deficits - Sanei Taheri, Morteza; Haghighatkhah, Hamidreza; Azhideh, Arash; Arab Ahmadi, Mehran (International Clinical Neuroscience Journal, 2020)
Cervical spine fractures are common fractures due to spine trauma. Odontoid fracture is responsible for 20% of cervical spine fractures. Vertebral artery injuries (VAIs) had widely focused in this setting due to its occurrence with upper cervical fractures. In our case of study, a 42-year-old female presented in the hospital’s emergency department with a history of cervical spine injury without neurological deficits. In further investigations, cervical spine X-ray, magnetic resonance imaging (MRI), and angiography were done to evaluate the possible injuries to the bone, spinal cord, and vascular structures surrounding the spine that eventuated in the accidental diagnosis of bilateral vertebral artery occlusion. This case of the study demonstrated the importance of diagnostic investigations that can evaluate in an emergency department and bilateral vertebral artery occlusion without neurological symptoms due to collateral arteries establishment.